Identifikasi Pupa Jantan dan Pupa Betina dengan Metode Pemisahan Berdasarkan Ukuran Tubuh Pupa Aedes aegypti - Ratih Ristyanti; Lintang Dian Saraswati; Retno Hestiningsih (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Sterile Insect Technique (SIT) is one of controlling dengue fever by releasing sterile male mosquitoes into the field, the stadium is best for irradiation is the pupa stage. Therefore, it takes technique separation of male and female pupa accurate. The purpose of this research is to calculate the accuracy of separation techniques based on body size pupae. The type of research is descriptive research with survey method. The sample in this research is the number of pupae were identified from the colonies maintained. After being separated for calculating the level of accuracy is maintained until the pupa turns into adult mosquitoes seen contamination in cage. The results is 600 males pupae and 600 females pupae were identified. Based on the calculation of the accuracy of each colony male and female pupa is 99.83% with a 0.17% contamination. Concluded that the level of accuracy of separation based on body size pupa pupa is quite high at 99.83%. Advice given to the researcher that can be checked again to pupa which have been separated so that no contamination in the colony pupae